Form and function of negation in German and Indonesian: Searching for equivalent construction of meaning - Triyono, Sulis; Sahayu, Wening; Margana, M. (Universitas Pendidikan Indonesia, 2020)
This study analysed form and function of negation in German including the complexity of negation construction in German and its equivalence in Indonesian language. This study was qualitative in nature, describing the nature of negation in German and Indonesian language in two books: Carolin Philipps’ German novel, Traume Wohnen Überall, and Liliawati Kurnia’s translation into Indonesian, Mimpi Selalu Indah as an instance of the negation realization in texts. The validity of the data was determined by experts’ judgment and the reliability of the data by interrater and intrarater estimation. The data were analysed by using a correspondential method with a referential sorting technique involving reference to negation construction as a determiner, and a distributional method with an element distribution technique and a marker reading technique. The analysis indicates that there are six negation forms with respective meanings in German characterized by semantic similarity along with grammatical differences in the negation constructions in German and Indonesian. The findings show that German negation construction is considerably more complex. However, the different degree of complexity does not substantially influence the meaning making process in both languages; rather. tend to be mutually complementary. The findings of this study inform the way in which the meaning transfer of German-Indonesian and Indonesian-German should be made regardless of the complex negation in German.